Grafting of CAG peptides and (polyethylene glycol) on unsaturated polyurethane films to promote selective adhesion and migration of urethral epithelial cells. Issue 31 (27th July 2021) - Xie, Jieqi; Shen, Kangmi; Zheng, Honghao; Yao, Yuejun; Chen, Yicheng; Gao, Changyou
Abstract : An unsaturated polyurethane film is grafted with a cell-resisting PEG layer and CAG peptides, resulting in a larger adhesion number and faster migration rate of urethral epithelial cells over fibroblasts. Abstract : Selective adhesion and migration of urethral epithelial cells (HUCs) over fibroblasts (FIBs) are very important in the reconstruction of the urethral epithelial layer and prevention of ureteral scarring and stenosis. In this study, unsaturated polyurethane (PPFU-CO-SS) films were co-grafted with a cell-resisting poly(ethylene glycol) (PEG) layer and HUC-selective Cys-Ala-Gly (CAG) peptides, whose physicochemical changes were confirmed by X-ray photon spectroscopy, fluorescence spectroscopy and water contact angle measurements. The adhesion and activation of platelets on the PEG/CAG grafted surface were significantly reduced compared to those on the PPFU-CO-SS, resulting in a similar status as that on a PEG-grafted surface. The HUC-selective material could obviously promote the adhesion and migration of HUCs. The ratio of the urethral epithelial cells to fibroblasts on the PEG/CAG grafted surface was nearly 3-fold that on the unmodified PPFU-CO-SS in a co-culture competitive environment. The urethral epithelial cells cultured on the PEG/CAG grafted surface also had the highest migration rate, which was 2.24-fold compared to that on the PPFU-CO-SS control.